2009
DOI: 10.9775/kvfd.2009.086-a
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical distribution of ınsulin-, glucagon-, and somatostatin-containing cells in the pancreas of the rat (Wistar albino)

Abstract: Pancreas in the vertebrates is subdivided into two parts: One of them is exocrine part where digestive enzymes are released and the other one is endocrine part where regulatory hormones are released into blood circulation 1 . The endocrine part, formed by the islets of Langerhans, is multihormonal unit composed of at least four types of cells; the insulin (B cells), the glucagon (A cells), the somatostatin (D cells), and the pancreatic polypeptide (PP cells) 2 .Insulin is synthesized in the B cells of the panc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…These produce digestive enzymes and regulatory hormones for carbohydrate metabolism, respectively. The endocrine sections are the Langerhans islets and distribution randomly into the exocrine sections (1)(2)(3). The pancreas of cats is formed of a right and left lobe making a U-shape close to the gastric pylorus, and it consists of the duodenal, gastric, anastomotic, and splenic lobes.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…These produce digestive enzymes and regulatory hormones for carbohydrate metabolism, respectively. The endocrine sections are the Langerhans islets and distribution randomly into the exocrine sections (1)(2)(3). The pancreas of cats is formed of a right and left lobe making a U-shape close to the gastric pylorus, and it consists of the duodenal, gastric, anastomotic, and splenic lobes.…”
Section: Introductionmentioning
confidence: 99%
“…The islets of Langerhans in cats contain 4 different endocrine cells, similar to other mammalian species (4)(5)(6). These cells release regulatory hormones including glucagon (A, alpha, A 2 cell), insulin (B, beta cell), somatostatin (D, delta, A 1 cell), and pancreatic polypeptide (PP, F cell) (1,2,(7)(8)(9)(10)(11)(12)(13). Some researchers have also reported that the islets of Langerhans may contain nonspecific endocrine cells such as neuropeptide Y, substance P, galanin, cholecystokinin-8 (11), serotonin (10,14), gastrin, and ghrelin-releasing cells (15).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Somatostatinimmunoreactive cells among endocrine cells (islets of Langerhans) in the pancreas were determined by immunohistochemical and morphometric studies. It was claimed that somatostatin-immunoreactive cells were rare among endocrine cells (islets of Langerhans) in the pancreas and that these cells were localized especially in the peripheral regions of islets of Langerhans [25,26] . Our study showed that somatostatinimmunoreactive cells were localized in the peripheral region of the endocrine parts and TQ administration increased somatostatin release in the endocrine cells.…”
Section: Discussionmentioning
confidence: 99%